2017
DOI: 10.3892/etm.2017.5373
|View full text |Cite
|
Sign up to set email alerts
|

An oral formulation of cilostazol nanoparticles enhances intestinal drug absorption in rats

Abstract: Abstract. Cilostazol (CLZ) is an anti-platelet agent that is generally used after the onset of cerebral infarction. However, CLZ is a poorly water-soluble drug and a strategy for increasing its bioavailability is required. In the present study, novel oral formulations were designed containing CLZ solid nanoparticles to improve bioavailability. The present study investigated the therapeutic effect of the oral formulations containing CLZ nanoparticles on ischemic stroke using a cerebral ischemia/reperfusion-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…It is reported that nanoparticles from organic compounds are able to move through the spaces between the cells (28). In a previous study, we reported that recrystallization was suitable for the preparation of nanocrystals by using mill methods (16). These results suggested that the CLZ released from the CLZ nano gel patches was in a nanocrystal state.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…It is reported that nanoparticles from organic compounds are able to move through the spaces between the cells (28). In a previous study, we reported that recrystallization was suitable for the preparation of nanocrystals by using mill methods (16). These results suggested that the CLZ released from the CLZ nano gel patches was in a nanocrystal state.…”
Section: Discussionmentioning
confidence: 64%
“…We have previously designed drug nanocrystals by a combination of recrystallization and the breakdown method using a ball mill (16) and shown that CLZ nano enhanced drug bioavailability in the small intestine of rats (16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BA of the drugs carried by the nanoparticles shown to be increasing many folds. [26][27][28][29][30] The BA concept, blood levels will not be corroborated to the effect when the nanoparticles are developed for targeting specific organs or tissues in the body. In targeted nanoparticles, the drug might not appear in reasonable quantities in the blood, but the action would be mightier than the free drug.…”
Section: Distribution Of Nanoparticlesmentioning
confidence: 99%
“…[1][2][3] Cilostazol is used for the treatment of chronic arterial occlusive disease and intermittent claudication; cilostazol was developed by Otsuka Pharmaceutical Co., Ltd., and is commercially available as immediate-release (50 and 100 mg) or controlled-release tablets (200 mg) for the treatment of intermittent claudication. 6,7 In addition, a relatively large inter-subject variability is observed in the bioavailability of cilostazol after oral administration, and the coefficients of variation are approximately 40-60% for the area under the curve (AUC) and maximum concentration (C max ). 6,7 In addition, a relatively large inter-subject variability is observed in the bioavailability of cilostazol after oral administration, and the coefficients of variation are approximately 40-60% for the area under the curve (AUC) and maximum concentration (C max ).…”
mentioning
confidence: 99%